2008
DOI: 10.1021/ie071579d
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Filled Composite Porous Catalytic Particles for Hydrodynamic Studies in Trickle-Bed Reactors

Abstract: A simple and scaleable method is proposed for suppressing internal porosity in various porous particles that are widely applied in packed-bed catalytic systems. The method is based on a complete filling of the pores by a cross-linked organic polymer. The particles were first loaded with the volume of organic monomer and cross-linker needed to achieve complete blockage of the porosity, and subsequently, in situ radical polymerization was performed with heating under reduced atmosphere. The method is shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…However, CT scan failed to distinguish the external liquid holdup of alumina spheres. Aydin et al performed hydrodynamic studies in TBR packed with spheres of different contact angles, and found that the external liquid holdup was pretty close. This inspired us to replace the external static liquid holdup of alumina spheres with that of the glass spheres.…”
Section: Resultsmentioning
confidence: 99%
“…However, CT scan failed to distinguish the external liquid holdup of alumina spheres. Aydin et al performed hydrodynamic studies in TBR packed with spheres of different contact angles, and found that the external liquid holdup was pretty close. This inspired us to replace the external static liquid holdup of alumina spheres with that of the glass spheres.…”
Section: Resultsmentioning
confidence: 99%
“…Das Vermischungsverhalten in Rieselbettreaktoren kann anhand der Verweilzeitverteilung geeigneter inerter Tracer charakterisiert werden und wird nachfolgend hauptsächlich für die Flüssigphase beschrieben. Am gebräuchlichsten ist die Verwendung inerter löslicher Tracer wie beispielsweise Salze oder mischbare Substanzen mit von der Flüssigphase abweichenden und detektierbaren physikochemischen Eigenschaften (Härting et al 2015c;Aydin et al 2008;Hamidipour et al 2009).…”
Section: Rückvermischung Und Axiale Dispersionunclassified
“…bei dem die Abweichung von der idealen Propfenströmung durch den axialen Dispersionskoeffizienten quantifiziert wird. Bei porösen Partikeln muss der intrapartikuläre Stofftransport zusätzlich berücksichtigt werden (Aydin et al 2008…”
Section: Rückvermischung Und Axiale Dispersionunclassified
“…Hydroprocessing forms an essential unit process of petroleum refining to meet product specifications of prescribed limits of sulphur, aromatics, nitrogen, and olefins, as per environmental norms. [ 1–4 ] Hydroprocessing entails hydrotreating, which involves removing hetero compounds like sulphur, nitrogen, and oxygen, and saturation of aromatic rings and olefins. It also involves processes like hydrocracking, which disintegrates feed with high molecular weight into low molecular weight products.…”
Section: Introductionmentioning
confidence: 99%